The Opportunities of Rail in Freight Transport from China to Finland : Case Approach - Marttila, Maija-Stina (My University, 2019)
The purpose of this thesis is to evaluate the viability of railway transport in the transport of goods from China to Finland. In the past decades, China has experienced immense economic growth and in 2014, China surpassed the USA as the world’s number one economy. The demand for transport from China has naturally exploded. Heavy investments in infrastructure have been made, yet congestion is still a problem. The One Belt, One Road initiative launched by the Chinese Government in 2013 aims to improve road and rail connections from China to its trading partners. As a result of investments made in Eurasian railway connections, the previously modest share of railway transport has begun to grow rapidly. Railway freight now provides a midway alternative to expensive air freight and sluggish ocean freight in terms of both cost and speed. This thesis explores the costs and delivery times of railway freight and other transport modes when moving freight from China to Finland. This thesis was conducted as an assignment and it takes a single case approach. This thesis utilizes a single case approach by examining the costs and delivery times of transport modes in the context of a case company. Both qualitative and quantitative approaches are utilized in order to gain a holistic understanding of the individual case. The main sources of data used are requests for quotation, participant observation, archival records and discussions. The main finding of this thesis is that railway freight is a viable alternative to ocean and air freight. Railway freight takes roughly half the time of ocean transport and the costs are not considerably larger than those of ocean freight. Air freight is indisputably the fastest and most reliable transport mode, but also evidently the most expensive. The second important finding is that with all transport modes, the freight costs per unit go down significantly when order quantity is increased. When only considering transport costs, it is advisable to order largest possible quantities. The third finding is that when transporting very small quantities, parcel services are always the best option.
Keywords: transport, railway, freight